Defining and registering criminal offences and measures: standards for a European comparison - Jehle, Jörg-Martin; Harrendorf, Stefan; Aebi, Marcelo F. (Göttinger Studien zu den Kriminalwissenschaften, 2010)
The study presented in this book is a direct response to the needs for defining and registering criminal and judicial data on the European level. Based upon work done in creating the European Sourcebook of Crime and Criminal Justice Statistics (ESB), the project results will improve and complement the standards developed so far for definitions and statistical registration in four fields (police, prosecution, courts, prison), in order to contribute to the picture of criminal justice in Europe. Possibilities to optimize the offence definitions used so far in the ESB context were explored. Also, further crime types, especially those subject to EU-harmonized definition, were tested and introduced. Apart from this, the prosecution chapter of the ESB questionnaire was changed and expanded. Data collection possibilities regarding compulsory measures in the investigatory stage were tested, and a more sophisticated approach for recording sanctions and measures as well as prison data was developed. The study explored how far national statistics can provide such data and developed a concept for collation on European level. It was funded by the European Commission under the AGIS 2006 program.